Selection the optimum place of FACTS devices using fuzzy control system - Jawad Hameed; Hameed Ali Mohammed; Amer T. Saeed (Institute of Advanced Engineering and Science, 2020)
In this paper, the voltage stability of the power system is studied during fault conditions. Enhancement of the system’s stability will be achieved by utilizing Flexible AC transmission systems (FACTS) controllers at the best place in the system. The optimum placement of (FACTS) controllers occurred on the most affected bus by the fault in the system (weakest bus). Two approaches have been used in this study to effectively obtain the best location of the (FACTS) controllers in the system. The first method is based on computing the deviation which occurs in the active power and reactive power due to the fault at each load bus at a time. Whereas the second method is performed through exploiting a MATLAB fuzzy set technique utilizing two indices: Line Flow Index (LFI) and Voltage Profile Index (VPI) during fault and steady-state conditions. The results show that both of these indices resulted in the same bus as the best location. Remedial actions in the attempt at improving in the stability of the power system are discussed taking the advantage of using (FACTS) compensation (SVC) and (STATCOM) at the most vulnerable system buses. In this work, MATLAB program with an IEEE 24 bus system is examined.